A novel methodology for investigating foamy oil stability by an oil-based analogue model. Issue 2 (1st February 2018) - Sun, Xiaofei; Zhang, Yanyu; Fang, Xiao; Wu, Shiqi; Chen, Guangpeng; Jules, Buntu; Chen, Fuzhen
ABSTRACT: A novel methodology was developed based on oil-based foam to systematically investigate foamy oil stability. The first step was to generate an oil-based analogue model that has similar characteristics of foamy oil. Then, the effects of the key factors were investigated with the created oil-based foam by a new experimental procedure. Moreover, a statistical approach was utilized to ensure reliability of the experimental data. Finally, we proposed a new method to describe foamy oil rupture and simulate its defoaming kinetics. The results showed that the oil-based foam can be precursors to studies on actual foamy oil and other petroleum foams. GRAPHICAL ABSTRACT: